2019
DOI: 10.1002/pan3.10055
|View full text |Cite
|
Sign up to set email alerts
|

Linking farmer and beekeeper preferences with ecological knowledge to improve crop pollination

Abstract: 1. Pollination by insects is a key input into many crops, with managed honeybees often being hired to support pollination services. Despite substantial research into pollination management, no European studies have yet explored how and why farmers managed pollination services and few have explored why beekeepers use certain crops.2. Using paired surveys of beekeepers and farmers in 10 European countries, this study examines beekeeper and farmer perceptions and motivations surrounding crop pollination.3. Almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
1
31
0
2
Order By: Relevance
“…Different aspects of nature‐connectedness can be broadly understood as types or expressions of relational values (Chan et al., 2016, 2018), further to the instrumental values that respondents hold relating to crop pollination and food security (Breeze et al., 2019; Hanes et al., 2015; Park et al., 2020) and intrinsic values demonstrated previously (European Commission, 2018). However, our nature‐connectedness measures barely scratch the surface of the diversity of other relational values that may directly or indirectly influence a person's actions, such as attachments, commitments, responsibility and admiration, towards nature (Chan et al., 2016, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Different aspects of nature‐connectedness can be broadly understood as types or expressions of relational values (Chan et al., 2016, 2018), further to the instrumental values that respondents hold relating to crop pollination and food security (Breeze et al., 2019; Hanes et al., 2015; Park et al., 2020) and intrinsic values demonstrated previously (European Commission, 2018). However, our nature‐connectedness measures barely scratch the surface of the diversity of other relational values that may directly or indirectly influence a person's actions, such as attachments, commitments, responsibility and admiration, towards nature (Chan et al., 2016, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Different aspects of nature-connectedness can be broadly understood as types or expressions of relational values (Chan et al, 2016(Chan et al, , 2018, further to the instrumental values that respondents hold relating to crop pollination and food security (Breeze et al, 2019;Hanes et al, 2015;Park et al, 2020) and intrinsic values demonstrated previously (European Commission, 2018).…”
Section: What Influences People's Pollinator Conservation Behaviour?mentioning
confidence: 93%
“…The probability of the same occurring in say, South America or Asia-Paci c, was considered far lower, even if the severity of the impact would be similar ( Figure 2). Experts were divided (low agreement) on the risk from losing managed pollinators in Europe (Figure 2), where markets for pollination services are less well developed 50 , and South America, where the number of managed honeybee colonies has expanded substantially but pressures on their populations remain high 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Insect pollination increases oilseed rape (OSR; Brassica napus) yield [16][17][18], seed weight [18,19], and quality [13], indicating a strong interdependence between OSR and pollinators. Evidence is mounting that a range of insect-pollinated crops are experiencing pollination deficits (i.e., losses of yield/quality as a result of inadequate pollination services) [20,21], indicating that effective management of pollination services will have clear agronomic benefits [21]. OSR provides insects with nutrient-rich resources, producing nectar and pollen as a reward for insect-visitors in exchange for pollination services [22].…”
Section: Interdependence Of Oilseed Rape and Insect Pollinatorsmentioning
confidence: 99%